At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Since by the 2nd equation, we know that y is the same as 6-x, we can substitute that for y in the first equation:
y = 2x + 3 -> 6 - x = 2x + 3 -> 6 = 3x + 3 -> 3 = 3x -< x = 1 and by either of the two equations, that derives y = 5
Step-by-step explanation:
Answer:
ok you can use subsitution for this one
since y=2x+6
subsitute 2x+6 for y
3x-(2x+6)=6
3x-2x-6=6
add like terms
x-6=6
add 6 to both sides
x=12
subsitute
y=2x+6
y=2(12)+6
y=24+6
y=30
x=12
y=30
(x,y)
(12,30)
Step-by-step explanation:
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.